1978
DOI: 10.1093/bja/50.4.375
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic Studies During Induction of Anaesthesia for Open-Heart Surgery Using Diazepam and Ketamine

Abstract: In 14 patients undergoing open-heart operations the haemodynamic effects of diazepam 0.4 mgkg(-1) followed by ketamine 2 mg kg(-1) were studied. In eight patients undergoing coronary bypass surgery, the mean arterial pressure decreased significantly after diazepam from 90.3 +/-7.4 (SEM) to 78.0 +/-5.0 mm Hg (P less than 0.05). However, no changes occurred in six patients undergoing valve replacement. The subsequent administration of ketamine produced no significant changes in mean arterial pressure. No signfii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1984
1984
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 3 publications
0
11
0
1
Order By: Relevance
“…[10] Benzodiazepines are utilized to attenuate these effects. [11] In our study, midazolam was used in a fixed dose of 1 mg, and an increase in cardiac beats was found in three patients (Groups C and D) and an increased blood pressure in two patients of the same group.…”
Section: Discussionmentioning
confidence: 80%
“…[10] Benzodiazepines are utilized to attenuate these effects. [11] In our study, midazolam was used in a fixed dose of 1 mg, and an increase in cardiac beats was found in three patients (Groups C and D) and an increased blood pressure in two patients of the same group.…”
Section: Discussionmentioning
confidence: 80%
“…A number of investigators have demonstrated that fentanyl in doses of between 25-100 pgkg produces little or no change in most cardiovascular variables during induction of anesthesia (6-9), although Lunn and Stanley found significant decreases in mean blood pressure averaging 15 and 13% after 75 and 150 pgkg, respectively. Hemodynamic stability during induction of anesthesia with diazepam in doses ranging from 0.5 to 0.7 mgkg also has been well documented (1)(2)(3)(4)(5). However, Samuelson and McCowan found sighcant (11 and 10%) decreases in mean arterial pressure after induction with 0.5 mgkg diazepam.…”
Section: Discussionmentioning
confidence: 97%
“…Diazepam (1)(2)(3)(4)(5) or fentanyl (6-9) alone may be used to produce unconsciousness with little change in hemodynamic function. However, benzodiazepines are frequently combined with narcotic analgesics to provide hypnosis and amnesia.…”
Section: Heart-mentioning
confidence: 99%
“…Chudnofsky and colleagues justify their ketamine use in elders by citing two previous reports in which cardiac surgery patients showed cardiovascular stability with this drug. 22,23 These two reports, however, contained a mere 12 subjects with coronary artery disease, and the 95% confidence intervals for zero adverse events in this small sample actually range from 0% to 25%.…”
Section: Sympathomimetic Effectsmentioning
confidence: 99%